Production of polyhydroxy butyrate by chlorella pyrenoidosa and its application in food packaging - (:unkn) unknown (Calicut, 2024)
Most of the synthetic polymers produced from petrochemical resources are not biodegradable and newlineare generating serious environmental problems. Limitation of petrochemical resources with increase in oil newlineprice and environmental problems raises the interest for biopolymers. Polyhydroxyalkanoates (PHAs), newlinenaturally-occurring polyesters of various hydroxyalkanoates, are synthesized by a very broad range of newlinemicroorganisms as intracellular inclusions of carbon and energy reserve compounds under unbalanced newlinegrowth conditions. The current cost of PHA production is far greater in comparison to petrochemical newlineplastics. One way to reduce the production cost is the utilization of low cost raw materials, such as newlineindustrial wastes and by-products as carbon sources. newlineThe objective of this work is to produce polyhydroxybutyrate (PHB), using bacterial and algal newlinespecies from cheese whey. The bacterial strain in our study was isolated from food processing wastewater newlinecollected from dairy industry (MILMA) in Kozhikode. The isolated strains were screened for intracellular newlinelipid accumulation by staining with Sudan Black. Based on the morphological and physiological newlineproperties and sequence of its 16S rRNA, the selected polyhydroxyalkanoates accumulating strain SS9 newlinewas identified as P.putida (1,423 bp). The nucleotide sequence will appear in the GenBank nucleotide newlinesequence database under accession number MF403057. The algal strain used was Chlorella pyrenoidosa newline(NCIM 2738), fresh water micro algae, procured as a slantculture from the National collection of newlineindustrial microorganisms (NCIM), India. newlineFirst, batch tests in shake flasks were conducted with the selected strain in order to optimise this newlineprocess. The significant parameters such as pH, temperature, nitrogen source concentration were studied newlinein shake flask. Statistical design of experiments by the application of factorial experimental design in newlinemaximizing polyhydroxyalkanoate (PHA) production by optimizing major bioprocess variables was newlinestudied by Response Surface Methodology (RSM).
Keywords: Engineering; Engineering and Technology; Engineering Chemical